AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE NOVEL LOCKWOOD &CO: STREAMING STAIRCASE BY JONATHAN STROUD - Yoga Harnutomo; Intan Firdaus (IKIP Siliwangi, 2024)
A figurative language is a tool that allows us to understand the boundaries of literal words and feel the beauty of words hidden in them. With figurative language, we can also understand beautiful and soul-stirring images in sentences that contain figurative language. This research discusses figurative language and translation methods in the novel LOCKWOOD & CO: THE STREAMING STAIRCASE. This research focuses on four types of figurative language which are; Simile, Personification, Hyperbole, and metaphor. This research uses a descriptive qualitative to know the use of figurative language found in sentences and translation in the novel, This is because the qualitative method is a suitable method for answering existing questions and allows the collection of data that is rich in detail and context. In this research, the writer uses the theory according to Abrams to find out the types of figurative language and Newmark's theory to find out the translation method used in the novel the writer uses.